Road Weary? Testing Whether Long Commutes to Testing Sites Explain Deficient Cyber Charter School Academic Performance. Issue 3 (3rd July 2021) - Kingsbury, Ian; Maranto, Robert; Beck, Dennis
ABSTRACT: Cyber charter schools may increase access to a range of educational offerings, but they substantially underperform traditional public schools on measured academic performance, as demonstrated in a range of studies with distinct samples and methods. Artificial testing conditions offer a possible explanation. In contrast to face-to-face students, for cyber charter students standardized testing occurs in unfamiliar locations, often hours from the location of instruction (home), possibly leading to fatigue and lesser performance. Geocoding home locations and testing sites for 2015–18 mathematics, ELA, and science test scores from 5, 493 cyber school students in a northern state, we test whether drive times affect performance, controlling for student characteristics. Save for marginal statistical impacts on mathematics tests, we find no evidence that drive times affect cyber student measured academic performance. Implications are discussed.